European approach to promote democracy in the Arab region after Arab spring - زنودة, منى (مجلة الباحث للدراسات الأكاديمية, 2021)
The purpose of this paper is to outline the role of the European Union in supporting and promoting democracy in arab countries. Especially by tracking various initiatives and agreements that link the Union with the arab countries like the Euro-Mediterranean partnership, European Neighborhood policy…. achieving to the after 2011 period or which is called the arab spring. We have found through this study that the EU after 2011 has decided to resend its projects about reform and democracy issues in the arab world especially the so called the New-Neighborhood policy of 2015. Through this policy, the EU has changed the taken model of supporting democracy to a governance model based on multi-sectoral partnerships.